Evaluation of dental implant with hydroxyapatite coating by laser-induced hydrothermal synthesis: in vitro and in vivo experimental study - Lee, Jung-Tae; Kim, Sungtae; Lee, Sung-Ho; Han, Dong-Wook; Lee, Keonhee; Lee, Sangyun; Kwon, Daehyeok; Lee, Kyungwoo; Jeon, Hojeong; Jung, Tae-Gon; Kim, Bongju (SPRINGER, 2025)
Various surface modification techniques have been developed to improve the survival rate of dental implants. This study aimed to evaluate both in vitro and in vivo outcomes of implants coated with a nano/micro-assembled hydroxyapatite (HA) structure using a laser-induced single-step coating (LISSC) technique. Four types of implant surfaces were examined: machined surface implants (MA), sandblasted large-grit acid-etched implants (SLA), resorbable blasting media implants (RBM), and HA-coated implants (HA). In vitro analyses included surface morphology, surface hydrophilicity, and cell attachment. Twelve rabbits and two beagle dogs were used in the in vivo experiments. The implant stability quotient (ISQ) was measured immediately after placement and again at sacrifice (rabbits: 3 and 6 weeks; beagles: 12 weeks), followed by histological evaluation and quantification of bone-to-implant contact (BIC%) and bone volume (BV%). ISQ values increased from the postoperative period to 6 or 12 weeks across all implant types. In vitro, surface roughness ranked as HA > RBM > SLA > MA, while surface wettability ranked as RBM > HA > MA > SLA. No significant differences were observed in initial cell adhesion or viability among the groups. In vivo, BV ranked as MA > RBM > SLA > HA at 3 weeks, and MA > HA > RBM > SLA at 6 weeks. BIC ranked as RBM > MA > SLA > HA at 3 weeks and HA > RBM > SLA > MA at 6 weeks. HA exhibited the greatest increases in both BV and BIC from 3 to 6 weeks. In beagles, ISQ at 12 weeks was higher than baseline for both SLA and HA, with HA demonstrating superior BV compared to SLA. Within the limitations of this preclinical study, HA-coated implants produced via the LISSC method demonstrated comparable or superior biological performance relative to conventional MA, SLA, and RBM surfaces.